Language Learning Issues of Non-Reader in Rural and Urban Senior High School: A Comparative Analysis - Juharto L. Usop (RIRAI Publisher, 2024)
The general objective of this study is to assess the language learning difficulties of non-readers in rural and urban senior high schools in the Division of Cotabato City in the School Year 2022-2023. The purpose of this study is to examine the effects of environmental context, including resource and teacher support, on language development of the learners with poor literacy skills. The research design used was qualitative and the study used a thematic analysis to elicit the experiences of 30 non-readers from rural and urban schools. The data was collected through interviews, focus group discussions and classes observation. The research shows that non-readers in the rural and urban areas have basic problems, including inadequate literacy skills and poor participation in language learning activities. However, there was inequality in the distribution of resources and the level of support received by teachers where urban schools were found to have better resources and teachers’ training than the rural ones. Other factors that added to the difficulties of non-readers, mainly the home environment and peer relations, were worse in rural areas. Therefore, the study underlines the necessity of developing specific measures to approach the issues of non-readers. The enhancement of the vocabulary, resource distribution, and teacher training should be the strategies that aim at eradicating the inequality that exists in the education systems especially for students with different literacy levels or those in different geographical locations